MUC2 and MUC5AC Expression in Colon Cancer: A Preliminary Report from South India - Jayanth, R; Devaraj, H; Surendran, R; Jain, Mayank; Venkataraman, Jayanthi (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: There is scanty data from India regarding MUC protein expression from colorectal cancers (CRC) among Indian patients. Aim of the Study: The aim of this study is to assess the alterations in the expression of MUC2 and MUC5AC in 25 patients with CRC by site of the tumor location and differentiation at histology. Materials and Methods: Patients with proven adenocarcinoma of the colon alone were included for the study. Biopsy specimens obtained from tumorous lesions in the colon were classified based on histopathology as well differentiated, moderately, and poorly differentiated adenocarcinoma. Immunohistochemistry was done in the 4 μm thick sections to identify the expression of MUC2 and MUC5AC mucins. Results: MUC2 was uniformly expressed with near similar intensity while MUC5 was moderately (56%) to highly expressed (36%) in mucinous tumors. In nonmucinous tumors, MUC2 was least expressed (68%) with a significant expression on MUC5AC (88%). Except for rectosigmoid growth which had greater expression of MUC5AC (31%), both proximal and distal carcinomas had significant MUC2 and MUC5AC expression. Conclusion: MUC2 and MUC5AC are expressed in colonic cancers, the former showing mildtomoderate expression and the latter moderatetointense expression. The expression is more in mucinous adenocarcinoma.
Keywords: Cancer; colon; India; mucin